Neuromarketing, Subliminal Advertising, and Hotel Selection: An EEG Study. Issue 4 (November 2020) - Hsu, Liwei; Chen, Yen-Jung
This study aims to understand how hotel videos embedded with a smiling face emoji as a subliminal message affect consumers' selection of hotels, with their brain activities measured and collected while they watched the videos. Data was collected from sixteen participants who completed two rounds of experiments. A chi-square test of homogeneity, paired sample t -test, and Bayes factor were performed to address the two proposed research questions. The results of this study reveal that participants' selection of hotels would be significantly affected by the subliminal stimuli of a smiling face emoji. Meanwhile, neuroscientific data identifies significant differences between participants' two (theta and beta) out of five bands of brainwaves while they were viewing hotel videos with and without the subliminal message. Suggestions for future studies and practical operations are also discussed.